Isolation, cultivation, purification and identification of bacterial species from microfauna of soil (Italian Journal of Public Health, 2011)
Soil is an excellent source of unknown microorganisms since bacteria, algae, protozoans, yeasts, moulds,and microscopic worms are routinely found in this environment. Therefore, soil is a medium in which lifeis sustained in a fragile biological balance. Bacteria play an important role in nutritional chains that are animportant part of biological balance. In the present study, four different soil samples were collected fromthe rhizosphere of i) Sapota zapotilla, ii) Eucalyptus species, iii) Ficus religiosa from Lahore and iv) soil fromChanga manga, Pakistan. A Total of 28 bacterial species were isolated and classified in the period betweenNovember 2008 and December 2009. All species were cultured on recommended media for verification ofbiochemical characteristics. The results showed that at least fifteen Gram-positive bacterial species werepresent in samples and these were considered as the major group constituting the bacterial populationstrains.
Keywords: bacterial strains; soil; gram positive